Development of an efficient and thermally controlled Raman system for fast and safe molecular characterization of paint layers. (March 2018) - Mencaglia, Andrea Azelio; Osticioli, Iacopo; Siano, Salvatore
Graphical abstract: Highlights: A very efficient and safe portable Raman system was developed. High efficiency relies on a set of optical solutions which improve the signal. Side effects are prevented by power control driven by active thermal monitoring. The problem of rapid Raman characterization of photosensitive paint layers was solved. Abstract: An innovative high efficiency Raman system (exc. wav. 1064 nm) for safe molecular characterization of paint layers and other photosensitive materials has been developed and successfully tested. It was equipped with a novel optical probe, which has been designed and built in order to perform Raman scattering measurements on a relatively large spot at laser intensities lower than the typical ones of the commercial instruments. Original optical solutions were implemented in order to achieve such an improved efficiency. Furthermore, the instrument was also equipped with an active thermal control line allowing to prevent alterations of the material under study and to optimize the measurement cycles by means of suitable modulations of the laser power. Comparative tests using the novel analytical tool and an alternative setup based on a commercial Raman probe were carried out on a set of pure pigments and oil paint layers, which allowed assessing the significantly higher efficiency and reliability of the former with respect to the latter.